Arquitectura Empresarial de la Agencia Nacional de Infraestructura - ANI (2017)
This document contains the description of the work carried out, that is, the documentation of the Business Architecture of the National Infrastructure Agency, focused on the IT Architecture Reference Framework of Colombia proposed by the Ministry of Information Technologies and Communications - MinTIC. The repository of the Architecture is hosted on servers belonging to the National Infrastructure Agency and the information is confidential.